2018
DOI: 10.20944/preprints201811.0350.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Mannose-Binding Lectin Activation Help in Fighting Bacterial Pathogen in Poultry Production Systems?—A Review

Abstract: Bacterial pathogens have been attributed to poultry housing structure, financial strength, and incessant use of antibiotics, variable seasons and management systems practiced. Variant forms of bacterial pathogens can be detected by recognizing the molecular pattern of the pathogens through an innate immune mechanism such as mannose-binding lectin. Mannose-binding lectin (MBL) possesses an innate pattern recognition molecule that easily sequestered to region of infections and inflammations. This works by attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The neck domain initiates trimerization of the monomers which is stabilized by the intertwined collagen of MBL [ 9 , 20 ]. The trimer is considered the smallest active form of MBL (structurally, the smallest form of MBL) [ 20 ]. The N-terminal domains can covalently crosslink the MBL trimers via the cysteine residues, to higher oligomeric structures ( Figure 2 ).…”
Section: Mannose-binding Lectinmentioning
confidence: 99%
See 2 more Smart Citations
“…The neck domain initiates trimerization of the monomers which is stabilized by the intertwined collagen of MBL [ 9 , 20 ]. The trimer is considered the smallest active form of MBL (structurally, the smallest form of MBL) [ 20 ]. The N-terminal domains can covalently crosslink the MBL trimers via the cysteine residues, to higher oligomeric structures ( Figure 2 ).…”
Section: Mannose-binding Lectinmentioning
confidence: 99%
“…The N-terminal domains can covalently crosslink the MBL trimers via the cysteine residues, to higher oligomeric structures ( Figure 2 ). The International Union of Immunological Societies (IUIS) had not defined a specific oligomeric structure for MBL, and, in nature, several forms of MBL are present across animal species [ 9 , 19 , 20 , 21 ]. Laursen et al [ 22 ] observed that purified chicken MBL has a similar structure as mammalian MBL [ 9 , 19 , 20 , 21 ].…”
Section: Mannose-binding Lectinmentioning
confidence: 99%
See 1 more Smart Citation